Development of a vaccine against the synthetic opioid U-47700 - Park, Hyeri; Lin, Mingliang; Zhou, Jian; Eubanks, Lisa M.; Zhou, Bin; Janda, Kim D. (Frontiers in Pharmacology, 2023)
Opioid use disorders (OUD) and overdose have become a major public health concern in recent years. U-47700, a New psychoactive substance (NPS) opioid, also known as “pinky” or “pink” has been identified as a new threat in the drug supply because of its potency and abuse potential. Conjugate vaccines that can produce antibodies against target drug molecules have emerged as a promising tool to treat substance use disorders. Herein, we report the design, synthesis, and in vivo characterization of a U-47700 vaccine. The vaccine demonstrated favorable results with rodents producing elevated levels of antibody titer and sub-micromolar affinity to U-47700. In addition, antibodies generated by the vaccine effectively mitigated drug-induced effects by preventing the drug from penetrating the blood-brain barrier, which was verified by antinociception and drug biodistribution studies. The development of a vaccine against U-47700 and other NPS opioids contributes to the continued advancement of non-conventional pharmacological treatments to address the global opioid epidemic.